The Expression Pattern of Hypoxia-Related Genes Predicts the Prognosis and Mediates Drug Resistance in Colorectal Cancer - Yuan, Ye; Tan, Lulu; Wang, Liping; Zou, Danyi; Liu, Jia; Lu, Xiaohuan; Fu, Daan; Wang, Guobin; Wang, Lin; Wang, Zheng (Frontiers in Cell and Developmental Biology, 2022)
ABSTRACT Background: Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide. However, due to the heterogeneity of CRC, the clinical therapy outcomes differ among patients. There is a need to identify predictive biomarkers to efficiently facilitate CRC treatment and prognosis. Methods: The expression profiles from Gene Expression Omnibus (GEO) database were used to identify cancer hallmarks associated with CRC outcomes. An accurate gene signature based on the prognosis related cancer hallmark was further constructed. Results: Hypoxia was identified to be the primary factor that could influence CRC outcomes. 16 hypoxia-related genes were selected to construct a risk gene signature (HGS) associated with individuals’ prognosis, which was validated in three independent cohorts. Further, stromal and immune cells in tumor microenvironment (TME) were found to be associated with hypoxia. Finally, among the 16 hypoxia-related genes, 6 genes (DCBLD2, PLEC, S100A11, PLAT, PPAP2B and LAMC2) were identified as the most attributable ones to drug resistance. Conclusions: HGS can accurately predict CRC prognosis. The expression of the drug resistance-related genes is critical in CRC treatment decision-making.